Assessing securitisation and hedging strategies for management of longevity risk. (1st January 2011) - Gupta, Aparna; Wang, Haiyuan
In this article, we address the problem of developing a hedging strategy for managing a portfolio of longevity risk-sensitive products, such as annuities, term life insurance, using a shareholder value maximisation framework from a provider's perspective. An annuity provider extends a portfolio of annuities and is exposed to the cash flow requirements underlying this portfolio. Given the mortality risk of the demographics of its customer-base, the provider needs to develop a long-term risk profile of the cash-flow requirements of the portfolio, and develop a hedge for the scenarios where the necessary payments may threaten the provider's solvency. With a choice of newly emerging hedging instruments, such as mortality bonds, survivor swaps, longevity bonds, we assess the role these instruments can play in the risk management strategy of an annuity and/or insurance provider.